2023
DOI: 10.3390/ijms241310908
|View full text |Cite
|
Sign up to set email alerts
|

Association of Common Variants of APOE, CETP, and the 9p21.3 Chromosomal Region with the Risk of Myocardial Infarction: A Prospective Study

Abstract: The individual risk of an unfavorable cardiovascular outcome is determined by genetic factors in addition to lifestyle factors. This study was aimed at analyzing possible associations of several genetic factors with the risk of myocardial infarction (MI). For our study, we selected genes that have been significantly associated with MI in meta-analyses: the chromosomal region 9p21.3, the CETP gene, and the APOE gene. In total, 2286 randomly selected patients were included. Rs708272 and rs429358 and rs7412 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The ε3 allele was observed in 77.8% of individuals, the ε4 allele in 13.2% and the ε2 allele in 9%. Our data are in agreement with the results of researchers from around the world [ 12 , 14 , 15 ] as well as from domestic researchers [ 4 , 35 ]. For example, 70.4% had the ε3/ε3 genotype, 9% had the ε3/ε4 genotype, and 6% had the ε2/ε3 genotype, according to I.B.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ε3 allele was observed in 77.8% of individuals, the ε4 allele in 13.2% and the ε2 allele in 9%. Our data are in agreement with the results of researchers from around the world [ 12 , 14 , 15 ] as well as from domestic researchers [ 4 , 35 ]. For example, 70.4% had the ε3/ε3 genotype, 9% had the ε3/ε4 genotype, and 6% had the ε2/ε3 genotype, according to I.B.…”
Section: Discussionsupporting
confidence: 92%
“…The results of a recent review conducted by J. Alagarsamy et al showed that population studies revealed the association between APOE polymorphisms with increased risk of coronary and perivascular diseases [ 3 ]. In our recent study, we revealed a significant association of the ε2ε4 genotype of the APOE gene with MI ( p < 0.0001) [ 4 ], in agreement with the results of the review performed by J. Alagarsamy et al [ 3 ]. In 2021, A. Serrano-Pozo et al performed an analysis, confirming that the APOE ε4 allele is a genetic risk factor for sporadic Alzheimer’s disease [ 5 ].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Abnormal mutations in specific coagulation factors, such as fibrinogen ( FGA , FGB , FGG) ( 33 ), F2 ( 34 ), F5 ( 34 ), F7 ( 35 ), VWF ( 36 ), as well as genes in the fibrinolytic system like PLAT ( 37 ), and SERPINE1 ( 38 ), can lead to abnormal thrombosis or the formation of thrombi that are challenging to dissolve, subsequently increasing the risk of MI. Furthermore, genetic variants related to lipid metabolism and the inflammatory response are closely associated with the risk of MI, such as APOE rs7412 ( 39 ), CETP rs429358 ( 39 ), LPL rs328 ( 40 ), IL-6 rs1800795 ( 41 ), and TNF rs1800629 ( 42 ). These genetic variations can influence multiple biological processes, including cholesterol metabolism, vascular inflammation, plaque formation, and more, thereby increasing the risk of MI ( 43 45 ).…”
Section: Single-omics Approachesmentioning
confidence: 99%